A new species of Gegeneophis Peters, 1879 (Amphibia: Gymnophiona: Grandisoniidae) from the Western Ghats of northern Kerala, India - Kotharambath, Ramachandran; Vengot, Ranjith; Gower, David J. (Zootaxa, 2026)
A new species of grandisoniid caecilian amphibian, Gegeneophis bavali sp. nov., is described based on two specimens from northern Kerala state in the southern part of the Western Ghats region of peninsular India. This species is distinguished from all other Gegeneophis by the combination of lacking an unsegmented terminal shield, having secondary annular grooves, and having more than 132 primary annuli. A new key to the identification of the species of the genus is presented.